Joint association of METS-IR and uric acid with stoke, mediated by C-reactive protein - Jiang, Shan; Zhang, Xinyi; Song, Chengning; Wu, Guangfu; Yang, Aicheng (Frontiers in Endocrinology, 2024)
Objectives: To explore the dose-response relationship between the Metabolic Score of Insulin Resistance (METS-IR), uric acid (UA) and the risk of stroke incidence, the mediating role of C-reactive protein (CRP) in the above relationship, as well as the joint effect of METS-IR and UA on the risk of stroke incidence.Participants from the CHARLS study were included in this cohort study.Logistic regression models were used to estimate the odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for the associations of METS-IR and UA with the risk of incident stroke. The dose-response relationships of METS-IR and UA with stroke risk were assessed by restricted cubic spline regression. The mediation models were employed to estimate the potential mediating effects of CRP on the associations of METS-IR and UA with stroke risk. Logistic regression analysis was carried out to analyse the association of stroke and MRTS-IR combined with UA.Result: During a 9-year follow-up from 2011 to 2018, 570 incident cases of stroke were documented among 7,343 total participants. Per interquartile range increases in METS-IR and UA were associated with the increased risk of incident stroke, with the OR (95% CI) of 1.61 (1.44, 1.80) and 1.18 (1.05, 1.32) respectively. A dose-response function showed that METS-IR had a nonlinear relationship (P for nonlinear=0.047) and UA had a linear relationship (P for nonlinear=0.247) with the stroke risk. CRP had significant mediated effects on the associations of METS-IR and UA with stroke risk, and the proportion of mediation was 9.01% and 26.34% respectively (all P < 0.05). The results of joint effect showed that participants with high levels of METS-IR and UA had the highest increased risk of stroke compared to the participants with low levels of METS-IR and UA.METS-IR and UA levels were positively associated with an increased risk of stroke onset, and CRP mediated these relationships. Improving insulin sensitivity and regulating CRP and uric acid levels may be important for preventing the risk of stroke occurrence.